Industrialisasi dan Pengentasan Kemiskinan di Nusa Tenggara Timur: Pendekatan Analisis Data Panel - Ni Putu Lidya Pramesty; Firman Emmanuel Declarantius Parulian (Badan Pusat Statistik Provinsi NTT, 2025)
NTT is still facing a high level of poverty with slow progress in its reduction. One of the root causes of poverty in NTT is the low income of the population due to low labor productivity. In this regard, industrialization is considered a potential solution to poverty alleviation. However, previous studies on the impact of industrialization on poverty have shown varied results. Therefore, this study aims to provide an overview of industrialization in NTT and analyze its impact on poverty. This research uses panel data from 22 districts/cities between 2017 and 2023, sourced from Badan Pusat Statistik. The data is analyzed using descriptive methods and panel data regression. The results show that NTT has undergone an industrialization process, but at a low development rate. In fact, an increase in the contribution of the manufacturing sector to the economy has proven to be effective in reducing poverty in NTT's districts by enhancing labor productivity. However, merely increasing labor absorption in the manufacturing sector has not been sufficient to reduce poverty, particularly for low-skilled workers. This is because the manufacturing sector in NTT is still dominated by micro and small industries. Therefore, it is recommended that the government of NTT prioritize policies that focus on improving the quality of industries, especially micro and small industries.